Reconsidering the evidence: Are Eurozone business cycles converging - Michael Massmann; James Mitchell (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
This paper, using 40 years of monthly industrial production data, examines the relationship between the business cycles of the 12 Eurozone countries. Since estimates of the business cycle have been found to be sensitive to how the cycle is measured, a range of alternative measures are considered. We focus on both parametric and nonparametric univariate measures of the `classical' and `growth' cycles. We then investigate whether Eurozone business cycles have converged. This is based on an analysis of the distribution of bivariate correlation coefficients between the 12 countries' business cycles. This extends previous work that has tested for convergence, in a similar manner by focusing on correlation, but has not considered the entire distribution, instead focusing on the mean correlation coefficient or particular bivariate correlation coefficients. Although empirical inference about individual Eurozone business cycles is found to be sensitive to the measure of the business cycle considered, our measure of convergence between the Eurozone business cycles exhibits common features across the alternative measures of the business cycle. Interestingly, we find that there have been periods of convergence, identified by the distribution tending to unity, and periods of divergence. Although further data are required to corroborate the story, there is evidence to suggest that the Euro-zone has entered a period of convergence after the clear period of divergence in the early 1990s in the aftermath of German unification and at the time of the currency crises in Europe. This is encouraging for the successful operation of a common monetary policy in the Eurozone.
Keywords: 330